INNOVATIONS IN THE DESIGN-EDUCATIONAL SPACE - Romanenko, Natalia; Tarahtiy, Lesya (Sworld-Us Conference proceedings, 2025)
An analysis of innovative approaches in the design-educational space of training future teachers of higher education was carried out using the example of one of the best proposals for organizing the educational process by a master’s student, Tarakhtiy Les